The Bethesda system for reporting cervical cytology : definitions, criteria, and explanatory notes. - Solomon, Diane, ....-; Nayar, Ritu, ....- (New York : Springer, 2004)
This new edition of The Bethesda System for Reporting Cervical Cytology has been extensively updated and revised to reflect the new 2001 Bethesda terminology as well as methodological advances in cervical cytology. The handbook has now been expanded to include more than 185 full color illustrations (three times the number of color images in the first edition). New to the Second Edition are sections that address ancillary testing, including HPV, the inclusion of educational notes and recommendations, computerized screening, and anal cytology, as well as sample reports. In line with recent advances, the text and images will address liquid-based cytology in addition to conventional cytology. In addition to its user-friendly outline format, the inclusion of an index will allow the reader easier access to the information. A must-have for pathologists, cytopathologists, pathology residents, cytotechnologists, and clinicians.